The DNA replication-related element (DRE)/DRE-binding factor system is a transcriptional regulator of the Drosophila E2F gene. - Sawado, T.; Hirose, F.; Takahashi, Y.; Sasaki, T.; Shinomiya, T.; Sakaguchi, K.; Matsukage, A.; Yamaguchi, M. (Journal of Biological Chemistry, 1998)
Two mRNA species were observed for the Drosophila E2F (dE2F) gene, differing with regard to the first exons (exon 1-a and exon 1-b), which were expressed differently during development. A single transcription initiation site for mRNA containing exon 1-b was mapped by primer extension analysis and numbered +1. We found three tandemly aligned sequences, similar to the DNA replication-related element (DRE; 5'-TATCGATA), which is commonly required for transcription of genes related to DNA replication and cell proliferation, in the region upstream of this site. Band mobility shift analyses using oligonucleotides containing the DRE-related sequences with or without various base substitutions revealed that two out of three DRE-related sequences are especially important for binding to the DRE-binding factor (DREF). On footprinting analysis with Kc cell nuclear extracts and a glutathione S-transferase fusion protein with the N-terminal fragment (1-125 amino acid residues) of DREF, all three DRE-related sequences were found to be protected. Transient luciferase expression assays in Kc cells demonstrated that the region containing the three DRE-related sequences is required for high promoter activity. We have established transgenic lines of Drosophila in which ectopic expression of DREF was targeted to the eye imaginal disc cells. Overexpression of DREF in eye imaginal disc cells enhanced the promoter activity of dE2F. The obtained results indicate that the DRE/DREF system activates transcription of the dE2F gene.